Open innovation driven by hackathon: A social innovation case - Colenci Neto, Alfredo (2021)
Worldwide, the digital transformation has had a rapid impact on all types of organizations, whether industrial, commercial or service providers, including non-governmental organizations. In this context, organizations struggle to sustain their innovation efforts. A hackathon is one of the tools that can help the search for innovation in alignment with the principles of open innovation. It consists of an event in which participants collaborate intensively for a short period of time on projects focused on solving problems and generating ideas. These events encourage creative experimentation and can be challenge-oriented, including awards. Although the hackathon phenomenon emerged as an effective approach to foster innovation with digital technologies, it has gone beyond the field of computing and currently reaches other sectors that promote such events as a way to find solutions to real problems. This article presents a bibliographic study on hackathon and open innovation topics, and results from a field research carried out through the application of a hackathon for students in the business management course of a technology college in a third sector organization located in the city of São Carlos/SP, which had been suffering constant challenges to remain sustainable. The results show that this type of event can be an intense generator of ideas for problem solving in all, seven projects were created by a group of 47 students participating in a 32-hour marathon which had a positive impact on the institution.